1997
DOI: 10.1152/ajpendo.1997.272.5.e824
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolism and distribution of rabbit heparin cofactor II and rabbit antithrombin in rabbits

Abstract: The metabolic characteristics of two rabbit plasma thrombin inhibitors, heparin cofactor II (HCII) and antithrombin (AT), have been compared in healthy young rabbits. Purified HCII and AT-alpha were differentially radiolabeled (125I, 131I) and injected intravenously; blood samples were taken at prescribed intervals over 7 days. From the plasma clearance curves of protein-bound radioactivities, fractional catabolic rates and compartmental distributions were calculated using a three-compartment model. The whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The apparent discrepancy between the results of these 2 studies may reflect differences in study design (prospective vs crosssectional), the age or ethnic background of the subjects, the clinical end point (symptomatic coronary heart disease vs carotid atherosclerosis), or the assay method (activity vs antigen). Furthermore, studies on the distribution of radiolabeled HCII in humans 28 or rabbits 29 suggest that 40% to 60% of the HCII equilibrates into compartments outside the bloodstream. Thus, the plasma HCII concentration may not reflect the total amount of HCII present in specific vascular beds.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent discrepancy between the results of these 2 studies may reflect differences in study design (prospective vs crosssectional), the age or ethnic background of the subjects, the clinical end point (symptomatic coronary heart disease vs carotid atherosclerosis), or the assay method (activity vs antigen). Furthermore, studies on the distribution of radiolabeled HCII in humans 28 or rabbits 29 suggest that 40% to 60% of the HCII equilibrates into compartments outside the bloodstream. Thus, the plasma HCII concentration may not reflect the total amount of HCII present in specific vascular beds.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported, however, that HCII is present in the intima of normal human arteries 42 and that radiolabeled HCII is taken up into the intima or media of the intact rabbit aorta. 37 Nevertheless, it is clear from our immunohistochemical experiments that much larger amounts of HCII enter the arterial wall following endothelial injury.…”
Section: Discussionmentioning
confidence: 77%
“…Other investigators have reported, however, that HCII is present in the intima of normal human arteries 42 and that radiolabeled HCII is taken up into the intima or media of the intact rabbit aorta. 37 Nevertheless, it is clear from our immunohistochemical experiments that much larger amounts of HCII enter the arterial wall following endothelial injury.The results of this study support a model in which HCII becomes activated by binding to DS in the arterial wall after disruption of the endothelium. This model is consistent with the observation that HCII Ϫ/Ϫ mice do not show signs of spontaneous thrombosis but develop thrombi more rapidly than wild-type mice after arterial injury 14 ; furthermore, the ability of recombinant HCII to restore the thrombosis time of HCII Ϫ/Ϫ mice to normal correlates with its ability to bind to DS in the arterial adventitia.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…GAGs, commonly heparin but also DS, are used clinically for both prophylaxis and treatment of thrombosis (34,35). The disadvantages of these GAGs, to differing degrees, include risk of bleeding (35)(36)(37)(38), resistance of clot bound thrombin, short intravenous halflife compared with the plasma protein inhibitors (antithrombin and HC), whose action they catalyze (24,25,39), and decreased activity due to binding to proteins in vivo (14,20,23). We have produced and investigated the properties of two HC-GAG covalent complexes (HCH and HCD), which have a number of desirable properties that suggest they may have clinical applications related to selective thrombin inhibition.…”
Section: Discussionmentioning
confidence: 99%